Isolation and Characterisation of Wheat/Thinopyrum elongatum Introgressions - Herek Besler, Sevgi (2023)
The world population is predicted to increase to approximately 10 billion by 2050 and due to this increase 50% more food will need to be produced. Hexaploid bread wheat (Triticum aestivum, AABBDD, 2n=6x=42) is a major food source as cereals play an important role in the human diet. Wheat breeders have had considerable success in increasing production during the last century but now yields are starting to plateau. Bread wheat evolved nearly 10,000 years ago but domestication has reduced its genetic diversity making wheat vulnerable to everchanging abiotic and biotic stresses. To widen wheat’s gene pool, new alleles from landraces and wild relatives of wheat have been transferred through wide-crossing programmes. Thinopyrum species have been shown to be tolerant to many biotic and abiotic stresses such as drought and salt tolerance and leaf rust, yellow rust and Fusarium head blight resistance. As one of the Thinopyrum species, wheatgrass, Thinopyrum elongatum (EeEeEbEbExExStStStSt, 2n=10x=70), is an excellent reservoir for genetic diversity and can be used for the development of new wheat varieties. 116 wheat/Th. elongatum introgression lines were taken forward in this work with 191 crosses producing 1637 seeds and self-fertilisation of 801 of the backcrossed lines generating an estimated 60,441 seeds. Each subsequent generation showed higher levels of fertility as the wheat genome was restored. In this thesis, the production of the wheat-Th. elongatum introgression lines, containing segments of Th. elongatum of varying sizes, and their characterisation through Kompetitive Allele Specific PCR (KASPTM) markers is described. These lines were simultaneously examined with multi-colour and single-colour genomic in situ hybridisation (GISH) to determine the genomic constitution of the Th. elongatum chromosome(s) present. The KASP markers detected 530 introgressions across all seven linkage groups. In the majority of lines, the genotyping results were validated in the mc-GISH analysis. Genotyping with KASP markers allowed the rapid identification of introgressed segments and also the distinction between heterozygous and homozygous introgressions in the segregating populations. Twenty homozygous introgression lines were identified with the molecular characterisation, but more markers are required for the identification of small segments in those chromosome regions not as yet covered by the markers.